Fusobacterium necrophorum Brain Abscess Following Invasive Sinusitis in an Immunocompetent Adult: A Case Report - Andres V. Somoza; Christina T. Hanos; Jesse W. St Clair IV; Courtney L. James (Clinical Practice and Cases in Emergency Medicine)
Introduction: A brain abscess is a localized collection of purulent infection within the brain parenchyma. It most often occurs due to contiguous spread from sinus, otogenic, and odontogenic infections; however, it can also develop from direct intracranial contact via trauma or surgery. Fusobacterium necrophorum, an obligate anaerobic, gram-negative bacillus, is part of the normal flora of the oral cavity. Given its inherent location, F necrophorum has been shown to contribute to complications stemming from infection of the tonsils, pharynx, and teeth. Invasive infections of F necrophorum are seldomly seen in immunocompetent patients. Case Report: We report a case of a previously healthy 20-year-old man who presented to our emergency department with headache, facial pain, and neck stiffness. He was ultimately found to have an F necrophorum intracranial abscess and underwent right frontal craniotomy with evacuation of epidural abscess and partial sinus obliteration. He was placed on broad-spectrum antibiotics, including vancomycin, cefepime, and metronidazole for six weeks. His treatment course was complicated by recurrence of intraparenchymal abscess requiring repeat craniotomy with abscess evacuation and advancement of antibiotic regimen to meropenem. To our knowledge, there are no reported cases in the literature of monomicrobial F necrophorum brain abscesses arising secondary to invasive sinusitis in immunocompetent adults. Conclusion: This report highlights the clinical presentation, diagnostic strategies, management challenges, clinical outcomes, and complications of invasive sinusitis leading to brain abscess formation in an otherwise healthy adult male.